Harnessing the E3 Ligase KLHL12 for Tumor‐Selective Protein Degradation - Shicheng Xu; Xian Zhang; Shunbo Hu; Xinyi Wang; Yuxin Ge; Ziquan Zhao; Tianbao Zhu; Nan Wang; Limin Du; Qidong You; Xiaoke Guo; Zhengyu Jiang (Angewandte Chemie, 2026)
ABSTRACT Proteolysis‐targeting chimeras (PROTACs) are currently constrained by a reliance on ubiquitously expressed E3 ligases, which compromises tumor selectivity and raises toxicity risks. Here, we identified KLHL12 as a potentially tumor‐selective E3 ligase and reported the development of the first‐in‐class KLHL12‐recruiting PROTACs. Guided by a structure‐based macrocyclization strategy, we obtained a high‑affinity cyclic peptide, cp4 , as a KLHL12‑binding ligand and constructed novel PROTACs against oncogenic BRD4 and EGFR. The optimal compound k12bp‐1 achieved tumor‐selective BRD4(L) degradation in A549 cells, significantly inhibiting cell proliferation and driving cell apoptosis while sparing normal cells. It demonstrated robust in vivo antitumor efficacy in A549 xenograft mouse models without observable systemic toxicity. Collectively, this work established KLHL12 as a promising tumor‑selective E3 ligase and provided a KLHL12‐recruiting PROTAC platform for cancer therapy.